2017
DOI: 10.1016/j.contraception.2017.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Safety outcomes of female sterilization by salpingectomy and tubal occlusion

Abstract: TitleAbstract Objective: Compare immediate and short-term complications and surgical times among women having laparoscopic salpingectomy or tubal occlusion for female sterilization. Study design: We used billing data to identify women having laparoscopic sterilization at our training institution between July 1, 2011, and June 30, 2015. We performed a retrospective chart review to extract demographic information, surgical times and complications within 30 days, including unscheduled clinic or emergency room vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The characteristics and results of all included studies can be found in Table 1 . Six studies compared effectiveness [ 34 39 ]; 15 assessed adverse effects [ 17 , 18 , 34 , 35 , 38 48 ]; three compared patient recovery [ 18 , 35 , 44 ]; five compared non-contraceptive benefits, primarily the reduction of cancer risk [ 43 , 49 52 ]; six compared tolerability [ 34 , 35 , 37 39 , 52 ]; four compared costs to the healthcare system; [ 38 , 53 55 ] and seven compared length of procedures [ 17 , 18 , 38 , 44 , 47 , 48 , 55 ]. No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics and results of all included studies can be found in Table 1 . Six studies compared effectiveness [ 34 39 ]; 15 assessed adverse effects [ 17 , 18 , 34 , 35 , 38 48 ]; three compared patient recovery [ 18 , 35 , 44 ]; five compared non-contraceptive benefits, primarily the reduction of cancer risk [ 43 , 49 52 ]; six compared tolerability [ 34 , 35 , 37 39 , 52 ]; four compared costs to the healthcare system; [ 38 , 53 55 ] and seven compared length of procedures [ 17 , 18 , 38 , 44 , 47 , 48 , 55 ]. No included studies compared accessibility, eligibility, or follow-up required.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies assessed adverse effects. Results are organized by comparison: six compared hysteroscopic tubal occlusion and laparoscopic tubal ligation [ 34 , 35 , 38 41 ], two compared laparoscopic tubal ligation and a control [ 42 , 43 ], five compared laparoscopic tubal ligation and bilateral salpingectomy [ 17 , 18 , 44 , 45 , 48 ], one compared hysteroscopic tubal occlusion, laparoscopic tubal ligation, and bilateral salpingectomy with controls [ 46 ], and one compared bilateral salpingectomy with laparoscopic tubal ligation and with historical matched controls [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Female tubal occlusive permanent contraception procedures are estimated to reduce a woman’s lifetime risk of ovarian cancer by 24% to 34% [5,6]; however, women undergoing salpingectomy have a 64% risk reduction for serous epithelial ovarian and primary peritoneal carcinoma compared with women who have tubal occlusion or no permanent contraception procedure [7]. Furthermore, recent studies have shown no increased surgical risks with salpingectomy compared to occlusive procedures during laparoscopy, except for a minimal increase in operative time [8,9], or during cesarean delivery [10]. Use of salpingectomy for permanent contraception is increasing during laparoscopic sterilization and cesarean delivery [11,12] and ACOG has acknowledged salpingectomy as an effective method of contraception that may provide ovarian cancer risk reduction [13].…”
Section: Introductionmentioning
confidence: 99%